2021
DOI: 10.2147/copd.s320841
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Effect of Gene–Gene Interactions Between GSTM1, CHRNA3, CHRNA5 and SOD3 Gene Polymorphisms Combined with Smoking on COPD Risk

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a multifactorial disorder which is affected by external and internal risk factors. People with no external risk factors may be significantly affected and develop pulmonary disease. The study aimed to define gene-gene and gene-environmental effects on COPD. Methods: A case control study involved 181 COPD patients and 292 healthy individuals, with peripheral blood sampling and adequate questionnaires. Genotyping was done with various types of PCR design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It has been shown that the frequency of GSTP1 rs1138272 TC genotype in COPD patients was significantly higher than in normal people (28.57% vs. 14.45%), indicating that the GSTP1 rs1138272 polymorphism may be associated with COPD risk (Korytina et al, 2009). In contrast, Ganbold C et al (Ganbold et al, 2021) concluded that GSTP1 rs1138272 polymorphisms are not correlated with COPD risk (OR = 1.38, p = 0.381). It is reported that the T/C variant of GSTP1 on exon 6 replaces Ala114 with Val114 without changing enzymatic activities (Watson et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been shown that the frequency of GSTP1 rs1138272 TC genotype in COPD patients was significantly higher than in normal people (28.57% vs. 14.45%), indicating that the GSTP1 rs1138272 polymorphism may be associated with COPD risk (Korytina et al, 2009). In contrast, Ganbold C et al (Ganbold et al, 2021) concluded that GSTP1 rs1138272 polymorphisms are not correlated with COPD risk (OR = 1.38, p = 0.381). It is reported that the T/C variant of GSTP1 on exon 6 replaces Ala114 with Val114 without changing enzymatic activities (Watson et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…The tightly linked gene-gene interactions were observed between EPHX1 and GSTP1 gene polymorphisms, and alterations in the combined EPHX1 - GSTP1 detoxification activity may affect COPD development ( Ganbold et al, 2021 ). In view of the relationship between GSTP1 and EPHX1 , we simultaneously investigated the correlation between GSTP1 polymorphisms and COPD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic obstructive pulmonary disease (COPD) is characterized by airflow limitation in the lungs and pulmonary tissue destruction, often stemming from persistent respiratory tract inflammation [ 1 ]. While tobacco smoking remains the primary risk factor, numerous other elements, such as exposure to irritants (biomass smoke, air pollution, and chemicals) and genetic factors (gene polymorphisms, epigenetic modifications, and transcription regulation), significantly contribute to COPD, resulting in diverse disease phenotypes [ 1 , 2 , 3 , 4 ]. Among the main genetic variations are polymorphisms in molecules, such as alpha-1 antitrypsin (AAT), tumor necrosis factor (TNF-α), matrix metalloproteinases (MMPs), or antioxidant enzyme genes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…But only about 20 percent of heavy smokers had developed COPD [3]. It is mostly explained by an individual's genetic factors, which are related and contributes to detoxification, oxidative stress and other smoking-induced inflammation process [4]. Moreover, a number of studies have found the evidence for the association between smoking and matrix metalloproteinases (MMPs) in COPD [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%